Analisis Strategi Pemasaran Produk Amanah dalam Upaya Menarik Minat Nasabah pada PT. Pegadaian Syariah Cabang Gorontalo - Wiwin Koni; Saifullah (Jurnal Ekonomi Islam, 2022)
This research aims to find out how the Trusted Product Marketing Strategy in An Effort to Attract Customer Interest and to find out whether the marketing strategy implemented by the Gorontalo Branch Sharia Pawnshop can increase the number of customers. This type of research is field research with a qualitative approach. The data source in this study consists of primary and secondary data obtained from interviews with Managers and Employees at Gorontalo Branch Sharia Pawnshop, and documentation and sourced from literature research in the form of reading books and other sources relevant to this research. This study resulted in the following findings: First, the marketing strategy used by Gorontalo Branch Sharia Pawnshop using 4P strategies: Products, Price, Place, and Promotion. Second, the marketing strategy that has been carried out by Gorontalo Branch Sharia Pawnshop was able to attract customer interest and increase the number of customers. This is evidenced by the increase in the number of customers of trust products from 2016-2019.